Photocatalytic water splitting for solar hydrogen generation: fundamentals and recent advancements - Yuan, Lan; Han, Chuang; Yang, Min-Quan; Xu, Yi-Jun (International reviews in physical chemistry, 2016)
The expected depletion of fossil fuel reserves and its serious environmental impact have emphasised the issue of sustainable development of the human society. Solar hydrogen by photocatalytic water splitting is a promising alternative to conventional fossil fuels, which is of great potential to relieve the energy and environmental issues and bring an energy revolution in a clean and sustainable manner. This review is going to make a brief introduction of the basic principles of photocatalytic water splitting and the concept of different kinds of water splitting systems. Various engineering strategies for searching higher efficiency of water splitting based on the photocatalytic processes, including light harvesting, charge carriers separation and co-catalysts loading, have been outlined and discussed with selected typical examples on some elaborately designed semiconductor-based photocatalytic systems. Moreover, recent impressive progresses and advancements for photocatalytic water splitting with some promising materials are presented. Finally, this review is concluded with a summary and perspective in this hot area of research.